The Meaning and Formation of the Japanese Compound Verb ～tomeru (～留める) - Taulia; Yusuf, Muhammad (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2023)
This study discusses "Compound Verbs ~tomeru (～留める) in Japanese Sentences." The purpose of this study is to describe the structure and meaning of the compound verb tomeru as it appears in Japanese sentences. The data consists of a variety of sentences containing the compound verb ~tomeru that were taken from a Japanese news website. This study collects data through the use of library techniques. The structure and meaning of the compound verb tomeru were then analyzed using the apportion method (agih) in conjunction with the basic technique for direct elements. The data analysis indicates that the compound verb tomeru is most frequently associated with progressive verbs. Volitional verbs can also be attached to the compound verb ~tomeru. The compound verb ~tomeru has seven meanings which are divided into five meanings that express the progressive aspect and two meanings that express the perfective aspect.